2021
DOI: 10.22161/eec.62.2
|View full text |Cite
|
Sign up to set email alerts
|

Strategic leadership effectiveness and its influence on organizational effectiveness

Abstract: This paper aims to explore the link between sustainable competitive advantage and strategic effectiveness, Erbil was selected as the place to carry out the research at small and medium-sized businesses. current studies are assessing the impact of strategic absorbency (ability), capacity to adjust strategies, and managerial wisdom on small and medium-sized companies in the Kurdistan region of Iraq's competitive advantage a separate regression analysis was used to quantify the impact of each independent variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…Thus, they are strong sources of managerial and sustained competitive advantage (Lincoln & Guba, 1985). There is a significant relationship between leadership and perceived organisational effectiveness (Ahmad et al, 2020;Ali & Anwar, 2021), as reflected in the findings of this study.…”
Section: Discussionsupporting
confidence: 61%
“…Thus, they are strong sources of managerial and sustained competitive advantage (Lincoln & Guba, 1985). There is a significant relationship between leadership and perceived organisational effectiveness (Ahmad et al, 2020;Ali & Anwar, 2021), as reflected in the findings of this study.…”
Section: Discussionsupporting
confidence: 61%
“…In a study conducted by Ali and Anwar entitled the effectiveness of transformational leadership and its effect on organizational effectiveness, the results showed that transformational leadership using the recruitment strategy has the greatest impact on organizational effectiveness and sustainable competitive advantage. While managerial wisdom has the least impact on organizational effectiveness [30]. Shao in examining the Interaction effect of strategic leadership behaviors and organizational culture on IS-Business strategic alignment and Enterprise Systems assimilation concluded that Leadership behaviors of ideal influence and inspirational motivation are important drivers of strategic coordination of information systems and business that have a positive effect on the compatibility of organizational systems [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Auctioneers can use these capabilities to influence and direct the work of multiprofessional teams [13]. Influence is a part of leadership and a process.…”
Section: The Influence Of Leadership Provides Direction For the Teammentioning
confidence: 99%
“…The auctioneer should try to avoid ambiguity when proposing changes to the team. For example, the price of the auction items should be determined according to the opinions of the multi-professional team [13]. The auctioneer needs to collect the opinions of customers in the exhibition, modify the price given by the evaluation team, and give a definite price opinion.…”
Section: The Influence Of Leadership Provides Direction For the Teammentioning
confidence: 99%